2022
DOI: 10.1200/op.22.00104
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Health Disparities in Delay to Initiation of Intensity-Modulated Radiotherapy

Abstract: PURPOSE: Delays in initiation of radiotherapy may contribute to inferior oncologic outcomes that are more commonly observed in minoritized populations in the United States. We aimed to examine inequities associated with delayed initiation of intensity-modulated radiotherapy (IMRT). MATERIALS AND METHODS: The National Cancer Database was queried to identify the 10 cancer sites most commonly treated with IMRT. Interval to initiation of treatment (IIT) was broken into quartiles for each disease site, with the 4th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Similarly poor results are seen in diabetes and cancer diagnosis, care, and outcomes, among other diseases, for Hispanic/Latino individuals, American Indians/Alaskan Natives, and Asian Americans 25–29 . Adjusting for delays in care attenuates but does not eliminate these relationships, suggesting that the longer time it takes to initiate care only partially explains poor outcomes among minority patients 18–21 . Our results show that the combination of non‐White race/ethnicity and missed first visit is associated with a very low proportion of wound healing.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Similarly poor results are seen in diabetes and cancer diagnosis, care, and outcomes, among other diseases, for Hispanic/Latino individuals, American Indians/Alaskan Natives, and Asian Americans 25–29 . Adjusting for delays in care attenuates but does not eliminate these relationships, suggesting that the longer time it takes to initiate care only partially explains poor outcomes among minority patients 18–21 . Our results show that the combination of non‐White race/ethnicity and missed first visit is associated with a very low proportion of wound healing.…”
Section: Discussionmentioning
confidence: 66%
“…[25][26][27][28][29] Adjusting for delays in care attenuates but does not eliminate these relationships, suggesting that the longer time it takes to initiate care only partially explains poor outcomes among minority patients. [18][19][20][21] Our results show that the combination of non-White race/ethnicity and missed first visit is associated with a very low proportion of wound healing. However, patients who completed their wound care initiation visit as scheduled had similar outcomes regardless of race, indicating that efforts to successfully initiate wound care among non-White patients may result in improved wound healing.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We identified 12 articles addressing disparities in time to initiate treatment, and complete treatment. Of the 12 articles identified, 10 had findings that indicate the existence of a disparity for the Hispanic population in this area, [11][12][13][14][15][16][17][18][19][20] whereas 2 did not. 30,38 Studies identified a longer time from presentation to first RT treatment for those with Hispanic ethnicity compared with Non-Hispanic patients.…”
Section: Time To Treatment Initiation and Completionmentioning
confidence: 99%
“…They demonstrated that Hispanic patients, among other minority groups, were significantly more likely to have delayed initiation of treatment for nearly all disease sites compared with NHW patients, with Hispanic patients having a median time to treatment initiation of 76 days compared with a median time of 67 days for NHW patients (P < 0.01). 16 In addition to greater time to initiate treatment, it was also identified that Hispanic patients had greater amounts of time to complete RT. 19,20 Lamm and colleagues conducted a retrospective study on patients undergoing breast conservation therapy for early-stage breast cancer, evaluating the timely completion of adjuvant radiation with hypofractionated and conventional regimens.…”
Section: Time To Treatment Initiation and Completionmentioning
confidence: 99%